Immigration Law Enforcement Againts Abuse of Visa Residence Permits for Foreign Citizens in Buleleng Regency - Sudika Mangku, Dewa Gede; Rai Yuliartini, Ni Putu (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to examine and analyze law enforcement against foreign nationals who violate the immigration rules in Buleleng Regency and the supervision carried out by the Buleleng Regency immigration authorities to prevent misuse of foreign citizens' residence permit visas in Buleleng Regency. This type of research is empirical legal research. The sampling technique used in this study is non-probability sampling with purvosive sampling technique and analyzed using qualitative methods. The results of the study show that Law Enforcement Against Foreign Citizens Violating Immigration Rules in Buleleng Regency, is divided into 2 (two) namely: Immigration Actions in Administrative Forms and Immigration Actions in the Form of Litigation or Judicial Processes. Supervision of the Immigration Office of Buleleng Regency to prevent the Misuse of Foreign Citizens' Residence Permit Visas, includes 2 (two) ways, namely: Administrative Supervision and Field or Operational Supervision.